Implementasi Rule-Based System untuk Mengidentifikasi Status Aktivitas Fisik Mingguan dalam Platform Pelaporan Web untuk Siswa Sekolah Dasar - Aslam Dafa Fauzan; Purwono Hendradi; Dimas Sasongko; Endah Ratna Arumi; Emilya Ully Artha (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2026)
Low levels of physical activity and increasing sedentary behavior among elementary school students make it difficult for teachers and parents to monitor children’s physical activity when records are still kept manually. This study aims to develop a web-based physical activity reporting system that supports the process of recording, summarizing, and monitoring students’ physical activity on a daily and weekly basis. The study used the Waterfall development model, which includes needs analysis through observation and interviews, system design, implementation, and testing. The system was developed using Laravel, PHP, and a MySQL database. To determine students’ physical activity status, the system employs a Rule-Based System (RBS) based on World Health Organization (WHO) recommendations, whereby students are categorized as “Active” if their total physical activity duration reaches at least 420 minutes per week and as “Inactive” if it falls below that threshold. System verification was conducted through functional and integration testing, as well as a comparison between the system’s classification results and manual calculations using five test data scenarios. The test results showed a 100% level of agreement between the system’s output and manual calculations, including in boundary condition testing at 420 minutes per week. The developed system provides a structured mechanism for recording, reporting, and monitoring students’ physical activity, thereby supporting teachers and parents in obtaining more documented and systematic information about students’ physical activity.